1815 Nodding syndrome associated with onchocerca volvulus: a longstanding mystery solved?. (1st December 2017) - Ellul, Mark
Abstract : Nodding syndrome is an epileptic disorder which occurs in children in East Africa and is characterised by atonic, convulsive and atypical absence seizures and cognitive decline. The syndrome is epidemiologically associated with infection by the parasitic worm Onchocerca Volvulus, which causes river blindness. However, this pathogen is not thought to be neuroinvasive, and the pathogenesis of the syndrome was hitherto unknown. In a recent paper in Science Translational Medicine, a team from the National Institutes of Health led by Dr. Avindra Nath detected autoantibodies to leiomodin-1 more abundantly in patients with nodding syndrome compared with community-matched controls. The researchers localised leiomodin-1 in mouse brain to the CA3 region of the hippocampus, cerebellar Purkinje cells and cortical neurons. The autoantibodies were cytotoxic in vitro, and cross reacted with O.volvulus antigens. These are exciting findings suggesting that nodding syndrome may be an immune-mediated disorder driven by molecular mimicry, and raising the possibility that immune therapy may be beneficial for these patients.